Cubic Observer Based Robust Tracking Control of Single Link Manipulator (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The work presented here is aimed to design a cubic observer based state feedback controller for tracking control of single link manipulator . A cubic observer based novel state feedback controller is designed for  angular position  control. The dynamic model of the manipulator involves modeling of the flexible link and servo motor dynamics. The overall design has been elaborated under state space framework. A cubic error correction term is introduced in the Luenberger observer dynamics for fast convergence of steady state error. Robust stability criteria is obtained for the overall system using Lyapunov equation. Simulation study is performed using Python . An experimental validation of the proposed controller is carried out by Controller -In-Loop simulation using  Raspberry Pi 3B model and a geared DC servo motor . Experimental results are presented at the end of this paper.